Achieving relational outcomes in casual dining restaurants through consumer commitment. Issue 2 (25th January 2017) - Kim, Lisa Hyunjung; Kim, Dong Jin
Abstract : The purpose of the study is to identify how we can achieve positive word-of-mouth (WOM) and share of purchases through consumer commitment in casual dining restaurants. This study proposes the theory of organizational commitment and the framework of the relationship development process as the theoretical foundation to identify the antecedents of consumer commitment (i.e. identification, switching costs, and satisfaction), and tests the role of consumer commitment between its antecedents and relational outcomes (i.e. share of purchases and positive WOM). The results of the study support that commitment plays a partial mediating role in the relationship between its antecedents and share of purchases. In addition, commitment exerts a full mediating role on the effects of identification and switching costs on positive WOM intentions, while it plays a partial mediating role between satisfaction and positive WOM intentions. Managerial implications are discussed to maximize delivering relational outcomes based on consumer commitment and its antecedents.